Adsorption of the methyl green dye pollutant from aqueous solution using mesoporous materials MCM-41 in a fixed-bed column - Alardhi, Saja M. (Heliyon, 2020)
In this study, a Methyl Green (MG) dye pollutant was separated by Mobil Composition Matter No. 41 (MCM-41) in a fixed-bed continuous column with investigated three parameters, namely a bed height (2–6 cm), initial MG concentration (10–30 mgL(-1)) and a process flow rate (0.8–1.6 mL min(−1)). Results indicated that the highest bed capacity of 20.97 mg/g was obtained with respective to optimal values such as; 6 cm for a column height, 0.8 mL min(−1) for flow rate, and an initial MG concentration 20 mgL(-1). Furthermore, a quantity of the adsorbed pollutant decreased as the flow rate increased, while increasing the initial MG concentration yielded the opposite effect. The column apparatus was performed properly at the low flow rate, whereas both the breakthrough and exhaustion time increased with the bed depth. Thomas and Yoon-Nelson models were applied for predicting the breakthrough curves and calculating the characteristic factors of the laboratory fixed-bed adsorption column, which were beneficial for process design. Based on regression coefficient analyses, results of employing the Yoon-Nelson model was found to be superior to the Thomas one. Breakthrough performance indicated that MCM-41 was suitable for applications in continuous adsorption regimes for MG dye. The mesoporous MCM-41 was recovered effectively by calcinations and employed again for four times in the continuous system successfully.